PWE-033 Comparison Of Patient Experience Of Colonoscopy And Ct Colonography In The English Bowel Cancer Screening Programme. (9th June 2014) - Plumb, AA; Ghanouni, A; Rees, CJ; Hewitson, P; Miller, H; Bevan, R; Taylor, SA; Halligan, S; von Wagner, C
Abstract : Introduction: The English Bowel Cancer Screening Programme (BCSP) uses colonoscopy to investigate positive faecal occult blood test results. CT colonography (CTC) is employed if colonoscopy is infeasible. Patient experience is monitored with a questionnaire, posted 30 days after colonic testing. We used these to compare patient experience of CTC and colonoscopy. Methods: The study was approved by the BCSP Research Committee. Screenees tested between 1/1/11 and 31/12/12 and responding to at least one questionnaire item were included. Multiple imputation of missing data was conducted under the missing-at-random assumption. Likert scale data ("strongly agree" to "strongly disagree") were analysed via ordered logistic regression using test category (CTC or colonoscopy) as the predictor variable and age, gender, deprivation score, screening centre and screening result as covariates (results presented as odds ratios). Results: 79, 493 questionnaires were analysed; 61, 899 contained at least one response. 2, 119 CTC and 60, 581 colonoscopy questionnaires were included (some individuals completed both tests). There was no difference in results between complete-case analysis and multiply-imputed analysis. Understanding of test risks was greater for colonoscopy than CTC: 95.7% understood risks of colonoscopy vs 86.9% for CTC (odds ratio=1.88 95% CI: 1.71–2.07, p < 0.0001). Test benefits were also better understood for colonoscopy than for CTC: 98.2% understood colonoscopy benefits vs. 93.6% for CTC (OR=1.67 95% CI: 1.52–1.84 p < 0.0001). Just over one-quarter found CTC more uncomfortable than expected (25.7%), more than for colonoscopy (20.8%; OR = 1.34 95% CI: 1.24–1.46, p < 0.0001, Figure 1 ). Post-procedural pain showed no significant difference between tests (CTC = 14.6%, colonoscopy=14.3%; OR = 1.07 95% CI: 0.93–1.22, p = 0.35). More patients understood their colonoscopy result (97.0%) than CTC (90.5%, OR=2.19 95% CI: 1.99–2.41, p < 0.0001). Direct CTC-related complications were rare (n = 16; 0.5%) although a further 20 (0.6%) suffered complications from subsequent procedures provoked by CTC. Colonoscopy complication rates were similar (n = 779; 1.0%). Conclusion: Although CTC is generally well-tolerated, it is more frequently judged unexpectedly uncomfortable than colonoscopy. Similarly, while overall understanding of test risks, benefits and results is high, rates are lower than for colonoscopy. Post-procedural discomfort and complication rates are similar between both tests. Clear communication of the risks, benefits, procedural experience and results of CTC is required in the BCSP. Disclosure of Interest: None Declared.